Źródła nacjonalizmu kurdyjskiego w Turcji = The sources of Kurdish nationalism in Turkey - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The idea of Kurdish nationalism was typical of the political situation at the turn of the 20th century in both Europe and the Middle East. The slow fall of the monarchic system together with the growing weakness of the Ottoman Turkey, favoured the national aspiration of numerous, marginal at that time societies.
Keywords: Kurdowie; Turcja; nacjonalizm